THE EFFECT OF FERMENTED PAPAYA (Carica papaya L.) LEAF EXTRACT ON COMMERCIAL CARCASS PIECES OF KAMPUNG UNGGUL BALITBANGTAN CHICKENS - I.T., Perangin-angin; Siti, N.W.; Sukmawati, N.M.S. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study was targeted at observing the impact of administering papaya leaf extract on the percentage of commercial carcass cuts of KUB chickens which were carried out in the cage owned by Ni Komang Ari Susiani which is located in Banjar Dinas Dukuh, Demung Village, Tabanan Regency, Kediri District, Bali. This study was carried out over 8 weeks, from June-August 2023, using RAL/complete random design which included 4 measures and 4 replications. Each replication used 3 unsexed KUB chickens with an initial weight of 50 ± 5 g. The measures distributed are levels of fermented papaya leaf extract of 0%, 2%, 4% and 6% for each P1, P2 and P3 measure. This study looked at the percentage variables of the back, chest, lower dan upper thighs and wings. The results of this study show that the total percentage of chest carried out by P1, P2 and P3 is significantly (P<0.05) greater than P0 periodically 17.33%, 13.84% and 13.67%, but for the back, thighs bottom, top display and wings, non-significant comparison (P>0.05). Through the results of the study, it can be concluded that the distribution of fermented papaya leaf extract at the level of 2-6% can increase the percentage of chest with the best results at the level of 2%, but does not have an impact on theback, lower, upper thighs and wings.